Analisis Pengaruh Jarak Terhadap Kekuatan dan Stabilitas Sinyal Wifi di Area Gedung Kampus - Fitrian, Harry Pribadi; Sriastuti, Dini; Dede Rifki; Muhamad Rizki Yunara; Ari Aripin (Universitas Methodist Indonesia, 2025)
WiFi connectivity is crucial in supporting academic activities on campus, but its signal quality is affected by distance, physical obstacles, and Non-Line of Sight (NLOS) conditions. This study uses a Systematic Literature Review method to examine the influence of distance and environmental factors on the strength and stability of WiFi signals in campus buildings. The findings indicate that increased distance and the presence of physical barriers reduce RSSI and Signal-to-Noise Ratio (SNR) values, which subsequently decreases throughput and increases delay. Channel interference also contributes to connection instability. Optimization strategies such as proper access point placement and frequency channel management are essential to maintain network quality and ensure Quality of Service (QoS). This study provides strong indications of the key factors that need consideration in managing campus WiFi networks to support user comfort and usage efficiency.